Why so negative? Impacts and implications of US media coverage - Sacerdote, Bruce (Henry Stewart Talks, 2022)
Negative coverage, News, Covid-19, US media, Political polarization, Public mindset, Vaccination rates, Research, Funding, Social media, Local media, Policy, Industry, Media research